New geopolymeric binder based on fluid catalytic cracking catalyst residue (FCC) - Tashima, M. M.; Akasaki, J. L. [UNESP]; Castaldelli, V. N. [UNESP]; Soriano, L.; Monzo, J.; Paya, J.; Borrachero, M. V. (Elsevier B.V., 2012)
This paper provides information about the synthesis and mechanical properties of geopolymers based on fluid catalytic cracking catalyst residue (FCC). FCC was alkali activated with solutions containing different SiO2/Na2O ratios. The microstructure and mechanical properties were analysed by using several instrumental techniques. FCC geopolymers are mechanically stable, yielding compressive strength about 68 MPa when mortars are cured at 65 degrees C during 3 days. The results confirm the viability of producing geopolymers based on FCC. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: FCC; Geopolymer; Alkali-activated binder